Public sector reform : what works and why? : an evaluation of World Bank support (World Bank WashingtonUS, 2008)
Examines Bank lending and other support for public sector reform in four areas viz. public financial management, administrative and civil service, revenue administration, and anticorruption and transparency.
Keywords: FINANCIAL MANAGEMENT